Including the monetary part in macro accounting: A ‘modern’ approach to the macroeconomic accounting - TUTULMAZ, Onur (Journal of Economic Development, Environment and People, 2014)
Economic output is placed at the heart of the macroeconomics. To calculate the output one needs to achieve simplifying a high level complexity of economic relationships to form a system. On the flip side, the model should be enough elaborated to be able to reflect the important relationships. In this manner, the classical macroeconomic identity as Keynes suggested is simple enough to understand the main elements but it does not show the financial parts of transactions. Not having the monetary part of the economy it lacks the coherence. With the financial and economic crises getting more frequent, more endeavour to build a more inclusive and coherent macroeconomic system has been observed. However, there are large variety in different options of simplifying and simulating complex relationships among the real and monetary part of the modern economies. Our paper tries to set an analysis comparing some of the recent prominent ideas in building balance sheet and transaction flow matrix in regard to macroeconomic accounting system. We can conclude the new achievement of including the monetary transactions in the frame causes a compromise from the simplicity for a coherent and more complete picture of macro economy.